2021
DOI: 10.1108/jedt-01-2021-0033
|View full text |Cite
|
Sign up to set email alerts
|

A review of the significance effect of external factors of the solar dyer design to dried foods product quality

Abstract: Purpose The purpose of this paper is to present and discuss the external factors of the solar dryer design that influenced the thermal efficiency of the solar dryer that contribute to the better quality of dried food products. Design/methodology/approach From the reviewed works of literature, the external factors including the drying temperature, airflow rate and relative humidity have significant effects to increase the rate of moisture diffusivity of the freshly harvested products during the drying process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The drying process can minimize storage volume, avoiding waste and microbiological development and providing a longer shelf life for food products [3]. During the drying process, moisture from the inside of the products diffused up to the surface of the product before being evaporated to the surrounding chamber [4].…”
Section: Solar Drying Processmentioning
confidence: 99%
“…The drying process can minimize storage volume, avoiding waste and microbiological development and providing a longer shelf life for food products [3]. During the drying process, moisture from the inside of the products diffused up to the surface of the product before being evaporated to the surrounding chamber [4].…”
Section: Solar Drying Processmentioning
confidence: 99%
“…Drying on an industrial scale must ensure consistent quality with hygienic and uniform drying results (Hawa et al, 2021). The industrial drying processes must be rapid and efficient and provide uniform and hygienic dried product (D. Pagukuman & Wan Ibrahim, 2022). Previous studies regarding drying of herbs have been reported by various authors (Bhaskara Rao & Murugan, 2021; Thamkaew et al, 2021); However, limited information is provided about the drying kinetics of salam leaf.…”
Section: Introductionmentioning
confidence: 99%